A Study of inception and Growth of Civil Aviation in India - Mr. Gopal Chand, Dr. Dipti Ranjan Mohapatra (International Journal of Advanced Science and Technology, 2020)
Civil aviation sector in India is traversing through growth and development phase crossing many obstacles such as World wars, country’s independence, changes in government policies & economic outlook most importantly liberalization and other factors. Here an attempt has been made to present the growth of civil aviation sector in India since its inception. The role and support of regulatory agencies in the civil aviation domain has been elaborated in their present form. Most importantly the role of Directorate General of Civil Aviation (DGCA), Bureau of Civil Aviation Security (BCAS), Airports Economic Regulatory Authority (AERA) besides Ministry of Civil Aviation. The important role assigned by International Civil Aviation Organization (ICAO) to Airports Authority of India (AAI) in control and management of the Indian air space extending beyond the territorial limit of the country as accepted has also been discussed. There is a discussion about airports’ development and management mechanism taking into consideration the growth of civil aviation infrastructure in India, key initiatives under the National Civil Aviation Policy (NCAP) 2016 and Regional Connectivity Scheme (RCS). The paper presents historical account of more than a century long remarkable journey of Indian Civil Aviation sector.